Annual Report of the Librarian of Congress for the Fiscal Year Ending September 30, 1978 - Library of Congress, Washington, DC.; Library of Congress, Washington, DC. (Washington : Library of Congress, 1979)
Activities of the Library of Congress (LC), including the Copyright Office and the LC Trust Fund Board, are presented. The organizational structure of LC is presented, and the Network Development Office, the American Folklife Center, Federal Library Committee, Office of the General Counsel, and Management Policy Office are described in a report on the facilities, and exhibits, publications, and information activities of the Office of the Librarian. The Processing Department with its international program for acquisitions, developments in cataloging and processing, and staff activities is described, along with the Congressional Research Service and its programs, i.e., automated services, working relationships with other congressional support services, and divisions. A review of the Reader Services Department and its services, activities, publications, and exhibits is followed by the organization and preservation of collections, reference and bibliographic services, professional activities, and public events of the Research Department. The reader services, publications, and collection development of the Law Library are also included. The activities of the Administrative Department and the Copyright Office complete this report. The LC Trust Fund Board report, consisting of tables summarizing the major areas of financial obligation, and listings of exhibits, concerts, lectures, other programs, and LC publications are appended. (Author/MBR)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (Stock No. 030-000-00096-0).
ERIC Note: For related document, see IR 006 296.
Keywords: Library of Congress; Reports, Descriptive